The hermaphrodite sperm/oocyte switch requires the Caenorhabditis elegans homologs of PRP2 and PRP22 - Puoti, Alessandro (The National Academy of Sciences, 2000)
Sex determination in the hermaphrodite germ line of Caenorhabditis elegans is controlled posttranscriptionally. The switch from spermatogenesis to oogenesis relies on regulation of the fem-3 sex-determining gene via a regulatory element in the fem-3 3′ untranslated region. Previous work showed that at least six mog genes are required for repression by the fem-3 3′ untranslated region, and that one of those genes, mog-1, encodes a DEAH-box protein. In this paper, we report the cloning of mog-4 and mog-5 and the finding that mog-4 and mog-5 also encode DEAH-box proteins. Our molecular identification of mog-4 and mog-5 relied on genetic mapping and transformation rescue and was confirmed by a missense mutation in each gene. A phylogenetic analysis revealed that the C. elegans MOG-1, MOG-4, and MOG-5 proteins are closely related to the yeast proteins PRP16, PRP2, and PRP22, respectively. In view of their effect on fem-3 regulation and their homology to PRP16, PRP2, and PRP22, we propose that MOG-1, MOG-4, and MOG-5 are required for posttranscriptional regulation, perhaps by modifying the conformation of ribonucleoprotein complexes.